Effects of three tapering techniques on the performance, forces and psychometric measures of competitive swimmers - Hooper, S. L.; MacKinnon, L. T.; Ginn, E. M. (European Journal of Applied Physiology, 1998)
The data highlighted the importance of providing sufficient recovery before competition, since 1 week of reduced training was not long enough to maximise the benefits of tapering. However, none of the three types of tapering ( (a) reduced training frequency according to each athlete's daily ratings of well-being, (b) reduced training volume, and (c) reduced training volume and intensity) currently used by competitive swimmers could be shown to be more beneficial than the others.